A Note on Comparative Ambiguity Aversion and Justifiability. Issue 5 (September 2016) - Battigalli, P.; Cerreia‐Vioglio, S.; Maccheroni, F.; Marinacci, M.
Abstract : We consider a decision maker who ranks actions according to the smooth ambiguity criterion of Klibanoff, Marinacci, and Mukerji (2005). An action is justifiable if it is a best reply to some belief over probabilistic models. We show that higher ambiguity aversion expands the set of justifiable actions. A similar result holds for risk aversion. Our results follow from a generalization of the duality lemma of Wald (1949) and Pearce (1984).